Ethnobotanical inventory and therapeutic applications of plants traded in the Ho Central Market, Ghana - Boakye, Maxwell Kwame; Agyemang, Alfred Ofori; Turkson, Bernard Kofi; Wiafe, Edward Debrah; Baidoo, Michael Frimpong; Bayor, Marcel Tunkumgnen (Ethnobotany Research and Applications, 2022)
Background: For therapeutic purposes, local markets serve as the main trading center of medicinal plants for both traditional medicine practitioners and the general public. However, there is still limited information about the plant species and their derivatives traded outside larger markets in major cities. This study aimed to take inventory of the plant species traded for medicinal purposes in a traditional market outside a major city and determine their applications through vendors’ familiarization. Methods: An inventory of plant species traded for medicinal purposes in the Ho Central Market was undertaken, coupled with a semi-structured interviews on their applications based on the vendor's familiarization. Quantitative ethnobotanical indices were used to determine the most culturally important species. Results: A total of 60 plant species from 37 families was documented to be traded in the Ho Central Market. The Adansonia digitata, Thaumatococcus daniellii and Zanthoxylum zanthoxyloides were recorded to have the highest frequency of citations. The highest use report (UR) and cultural importance (CI) values were recorded for Z. zanthoxyloides. Body pains, blood tonic (anemia), and abdominal pains were the most prominent conditions that traded plants were used to treat. Conclusion: The study revealed a total of 60 medicinal plants which is commonly sold in the Ho Central Market and other major markets in the country, which was attributed to idiosyncrasy in cultural knowledge about the application of the plants. The market served as a venue for information exchange and learning, resulting in the high uniformity of vendors' familiarization with plant application and that of traditional medicine practitioners. Keywords: Local market, Medicinal plants, Trade, Cultural importance, Traditional medicine, Body pains